An Overview of Pare Rock Mass and Support System Design for Head Race Tunnel - Goswami, Pragati; Goswami, Diganta; Singh, Ranjeet Bahadur; Singh, Pawan Kumar; Kashyap, Sylvia (Advanced Aspects of Engineering Research Vol. 15, 2021)
The Upper-Siwalik Sub-Group of the Sub-Himalayan Range exhibits spatial heterogeneity with respect to geotechnical and geological properties which makes either the prediction of quality of rock mass or the characterization of the rock mass a difficult task. Although challenging, it is important to predict the general response of the rock mass to tunnel excavation. This paper attempts to characterize the Rock Mass around the Head Race Tunnel (HRT) of Pare Hydro-Electric Power Project in Arunachal Pradesh, India based on the classification systems viz. Rock Quality Designation (RQD), Terzaghi’s Rock Load Theory, Rock Structure Rating (RSR), Rock Mass Rating (RMR), and, Rock Mass Quality (Q) system. An attempt is also made to design the support system for the HRT of the proposed study area. A critical evaluation of the various support systems derived analytically from the above mentioned methods and that actually provided at the HRT is been made in the paper. This paper will assist other engineers in the design of support system for a rock mass using the outputs of various Rock Mass Classifications for similar rock conditions.